Red alert: Marxist approaches to science fiction cinema - Carneiro, Gabriel (2017)
this text points out the main aspects and approaches of the essays book Red alert: Marxist approaches to science fiction cinema, edited by Alfredo Suppia and Ewa Mazierska, which relates science fiction movies and the Marxist philosophy.